Plan estratégico para el mejoramiento de la gestión de la empresa Megatec, parroquia La Magdalena, cantón Chimbo, provincia Bolívar, período 2023-2027 - Vargas Ailla, Diego Lenin (2024)
The present research work is aimed at the elaboration of a strategic plan for the improvement of the management in the Megatec company, belonging to the Parroquia La Magdalena of the Canton Chimbo, during the period 2023-2027, whose purpose is to respond to the problems that are being presented due to the lack of strategies that allow it to achieve the objectives and the absence of an organizational philosophy, as well as responding to the demands of the clients for the quality of the service that is regular due to the fact that the speed of the network is It becomes slow at certain times of the day, causing delays for users in carrying out their activities, due to which there are no timely responses in real time.In such a way that in order to respond to these problems, a strategic plan model is proposed based on strategies for the optimization of resources and activities in the improvement of management, in this way the company Megatec will promote its growth by encouraging economic development. business in the sector to achieve the fulfillment of the objectives, through the formulation and application of long-term strategies and the development of an organizational philosophy.